(untitled) (Al-Mufassir: Jurnal Ilmu Alquran, Tafsir dan Studi Islam, 2024)
This studies examines the concept of nafs in QS. Asy-Syams 7-10 using Ferdinand de Saussure’s semiotic approach. The main issues discuss about the difference in interpretations among scholars which has led to various understanding about the concept of nafs in this surah. Previous studies have mostly focused on hermeneutical, psychological, or thematic analyses. This study employs a qualitative-descriptive approach, examining the elements of signs, signifiers, and signifieds in Qs. Asy-Syams verses 7–10, alongside the textual and contextual meanings of the verses. The findings reveal that nafs is intricately tied to all of Allah’s creations, which are designed to fulfill the soul’s needs. In this surah, nafs refers to the soul as a distinct entity, gifted by Allah with the potential to guide humans toward good or evil. This dual nature categorizes humans as either successful and fortunate if they purify their nafs, or as failures if they neglect it. Since humans are prone to error, the soul often becomes tainted, requiring continuous effort to keep it pure and aligned with righteousness.